Decomposability of topological groups - Zelenyuk, E. G. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We prove that every countable Abelian group with finitely many second-order elements can be decomposed into countably many subsets that are dense in any nondiscrete group topology.